2012
DOI: 10.1002/ceat.201200147
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Dynamics of Vibrofluidized Beds during the Transient Period of Water Evaporation and Drying of Solutions

Abstract: The influence of vibration number Γ, amplitude A, and frequency of vibration f on the fluid dynamic behavior of a vibrofluidized bed operating with inert particles in the transient period of water evaporation and drying of different solutions was evaluated. The solutions investigated were sewage sludge, skimmed milk, and calcium carbonate of three different solids contents. The impact of feed rate and vibration parameters on the dynamic behavior of variables such as pressure drop and inlet air velocity was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…However, at the low level of vibration strength ( K < 1), the drying curves poorly performed, with a reduction in the moisture content and a longer drying time compared to the case without vibration ( K = 1). These results, which agree with those of related studies, , indicated that the vibro-fluidized-bed dryer enhanced the drying performance only at certain ranges of K .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, at the low level of vibration strength ( K < 1), the drying curves poorly performed, with a reduction in the moisture content and a longer drying time compared to the case without vibration ( K = 1). These results, which agree with those of related studies, , indicated that the vibro-fluidized-bed dryer enhanced the drying performance only at certain ranges of K .…”
Section: Resultssupporting
confidence: 93%
“…During the separation process, lignite particles contained a high moisture content, although the air may remove a small amount of moisture. The stickiness of the lignite particles tended to be heightened by the amount of surface moisture ( M f ), which also increased particle agglomeration and prevented the onset of fluidization . This unbeneficial behavior could affect separation performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…e electrical energy consumed by blower and vibration motor in a vibro-fluidized bed dryer (VFBD) has been reported to be around 55% of the electrical energy of the blower in FBD [10]. Furthermore, by inducing vibration to the fluidized bed, homogeneous temperature circulation can be achieved [11], agglomeration of solid particles can be prevented and the fluidization velocity and pressure drop can be reduced [12,13].…”
Section: Introductionmentioning
confidence: 99%